Linking the Dynmod herd dynamics model with the Sector model within a partial equilibrium framework - Stepanyan, Davit; Bahta, Sirak T.; Enahoro, Dolapo K. (International Livestock Research Institute, 2023)
The purpose of this report is to outline the methodology employed in linking the Dynmod herd growth model (Lesnoff, 2008) converted into GAMS modeling language to a multi-market partial equilibrium model (SectorM) (Bahta et al., 2021) with a specific focus on bovine meat production. The report aims to provide insights into the linkage process and its technical implementation.